Analytical Study of Focus on Green Marketing and Caring Anvironronment by MN Cs in India - Gera , Navneet (Gyan Management Journal, 2012)
Green Marketing is the need of the environment due to limited resources and the growing population of «nnomy. The research paper envisaged the best practices adopted by corporate in green -.ering and the care taken by the Industrialist towards the environment. There are multiple eriges addressed by way of environment in this paper and the problems faced by the society in "DI due to environmental hazards. MNCs are contributing in multiple ways through their -::ured growth and the green marketing strategies. Many organizations want to turn green and -..e increasing number of consumers wants to associate themselves with environmental-friendly Governmental policies and regulations relating to environmental marketing has been mlly studied and addressed in this paper.